Analisis Realisasi Anggaran dan Pengelolaan Administrasi terhadap Efektivitas Pengembangan Sumber Daya Manusia (Studi Kasus BJB University) - Sifa Kholbiyati; Herry Sutanto (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the influence of budget realization and administrative management on the effectiveness of human resource development at BJB University. A qualitative approach with a case study design was employed through observations conducted during an internship in the operational division. Data were collected from direct observations of budget realization monitoring using the Internal Information System (SID), administrative documentation, and literature review. The findings indicate that budget realization has generally been implemented effectively, particularly for primary operational expenditures, although delays remain in several supporting budget components due to document verification, administrative completeness, and inter-unit coordination. Administrative management supported by the internal information system has improved document monitoring, yet its effectiveness is still influenced by the quality of administrative processes. The study concludes that budget realization and administrative management jointly contribute to enhancing the effectiveness of human resource development by strengthening organizational operational support.